Outcomes of Interventional-MRI Versus Microelectrode Recording-Guided Subthalamic Deep Brain Stimulation - Lee, Philip S.; Weiner, Gregory M.; Corson, Danielle; Kappel, Jessica; Chang, Yue-Fang; Suski, Valerie R.; Berman, Sarah B.; Homayoun, Houman; Van Laar, Amber D.; Crammond, Donald J.; Richardson, R. Mark (Frontiers in Neurology, 2018)
In deep brain stimulation (DBS) of the subthalamic nucleus (STN) for Parkinson’s disease (PD), there is debate concerning the use of neuroimaging alone to confirm correct anatomic placement of the DBS lead into the STN, versus the use of microelectrode recording to confirm functional placement. We performed a retrospective study of a contemporaneous cohort of 45 consecutive patients who underwent either interventional-MRI (iMRI) or microelectrode recording (MER)-guided DBS lead implantation. We compared radial lead error, motor and sensory side effect and clinical benefit programming thresholds, and pre- and post-operative Unified Parkinson’s Disease Rating Scale scores, and levodopa equivalent dosages. MER-guided surgery was associated with greater radial error compared to the intended target. In general, side-effect thresholds during initial programming were slightly lower in the MER group, but clinical benefit thresholds were similar. No significant difference in the reduction of clinical symptoms or medication dosage was observed. In summary, iMRI lead implantation occurred with greater anatomic accuracy, in locations demonstrated to be the appropriate functional region of the subthalamic nucleus, based on the observation of similar programming side-effect and benefit thresholds obtained with MER. The production of equivalent clinical outcomes suggests that surgeon and patient preference can be used to guide the decision of whether to recommend iMRI or MER-guided DBS lead implantation to appropriate patients with PD.